RELATIONSHIP BETWEEN BODY IMAGE PERCEPTIONS AND SELF ESTEEM AMONG TRIBAL ADOLESCENTS - P. SREEDEVI, S.BEULAH MARGARET AND (The Journal of Research, PJTSAU, 2019)
Adolescence is a period of life during which many important body changes take place that are determined by pubertal development. Adolescence is a time of great change not just markedby physical changes but also experiencing cognitive, social/ emotional and psychological changes. Physical and psychological changes can influence perceptions of satisfaction on their body image, there by influences the self-esteem and social adjustment of adolescents.